The Political Legacy of Abd al-Rahman al-Awza'i - Anke Iman Bouzenita (IIUM, 2008)
This statement of 'Abd al-Rahman al-Awza'i ( 88 - 156 A.H.), the great scholar fiqh and sunnah, is descriptive of his biography. This book depicts his life and, more particularly, his political legacy. It portrays a great scholar of the past as a role model for today's Muslims.